2022
DOI: 10.14744/agri.2021.04864
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ultrasound guided erector spinae plane block efficacy on post operative pain in lumbar spine surgery: a randomized clinical trial

Abstract: Objectives: Patients suffer notable levels of pain after lumbar spine surgery. The primary objective of this randomized clinical trial is to investigate the efficacy of erector spinae plane block (ESPB) on 24-h post-operative pain score of patients undergoing lumbar spine surgery. Cumulative opioid consumption and intraoperative bleeding were assessed as well. Methods: Adult patient candidates for elective lumbar spine surgery were randomly assigned to case (ESPB) and control (no ESPB) groups. The block was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Table 2 indicates that most prospective studies have demonstrated a statistically significant difference in opioid consumption in those receiving ESP block compared to traditional anesthesia ( 32 - 39 ). The pain-relieving effects of ESP block lowered opioid consumption compared to control and its effects lasted up to 48 hours post-surgery ( 32 , 34 - 39 ).…”
Section: Main Findingsmentioning
confidence: 99%
“…Table 2 indicates that most prospective studies have demonstrated a statistically significant difference in opioid consumption in those receiving ESP block compared to traditional anesthesia ( 32 - 39 ). The pain-relieving effects of ESP block lowered opioid consumption compared to control and its effects lasted up to 48 hours post-surgery ( 32 , 34 - 39 ).…”
Section: Main Findingsmentioning
confidence: 99%
“…The ESPB, an expansion on traditional modalities for postoperative pain control, was described by Forero et al in 2016 18 and its use in lumbar surgery continues to develop. In a randomized clinical trial, Nashibi et al 19 examined the efficacy of ultrasound-guided ESPB in postoperative lumbar pain control. The authors found that preoperative ESPB after the induction of general anesthesia significantly reduced pain scores, the need for rescue analgesia, and opioid consumption compared with controls.…”
Section: Postoperative Pain Management and Rehabilitation Protocolsmentioning
confidence: 99%
“…Posterior lumbar surgery is a common procedure to treat lumbar degenerative diseases (1). The surgery is traumatic and causes postoperative pain, which confines patients to the bed at the early stage, resulting in delayed recovery, prolonged hospital stays, and increased costs (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%